Study of acute toxicity of monocationic chlorin e6 derivative, a perspective photosensitizer for antimicrobial and antitumor photodynamic therapy - N. Yu. Zhidomorov; O. A. Nazarenko; V. I. Demidov; A. V. Kustov; N. V. Kukushkina; O. I. Koifman; A. K. Gagua; I. K. Tomilova; D. B. Berezin (Biomedical Photonics)
In this experimental work the acute toxicity of a chemically modified derivative of the natural pigment chlorophyll a called monocationic chlorin e6, which is a promising photosensitizer (PS) for antimicrobial and antitumor photodynamic therapy, was studied using white rats. The advantages of the PS under investigation are an intense absorption in the long-wavelength region of the visible spectrum, a sufficiently high quantum yield of singlet oxygen generation, pronounced amphiphilic properties along with an appropriate solubility in water, and a high level of photocytotoxic- ity in relation to both malignant HeLa cells and antibiotic-resistant hospital strains of E. сoli bacteria., P. aerugenosa and others. It has been shown that the value of LD50 of the considered PS can be calculated as the value of 100 mg/kg. In the reproduced experimental model of acute toxicity, pathomorphological changes in the vital organs of laboratory animals indicate a pronounced vasopathic effect of the drug with the development of cerebral edema and respiratory distress syndrome, which have become the main signs of thanatogenesis.